Preliminary evidence of a high risk of bleeding on aspirin plus clopidogrel in aspirin-naive patients in the acute phase after TIA or minor ischaemic stroke. - Geraghty, O; Kennedy, J; Chandratheva, A; Marquardt, L; Buchan, A; Rothwell, P (2010)
BACKGROUND: Aspirin plus clopidogrel (A+C) may be more effective than aspirin only (AO) acutely after TIA and minor stroke, but the risk of bleeding in the acute phase is uncertain. We determined this risk, focusing particularly on aspirin-naïve patients. METHODS: We studied consecutive referrals to the EXPRESS study clinic from 1/4/02 to 31/3/08. A 30- to 90-day course of A+C was given to patients presenting acutely. Bleeding events were identified by face-to-face follow-up, diagnostic coding, and blood transfusion data. Unpublished data from the FASTER pilot trial were also studied. RESULTS: Among 633 EXPRESS patients treated with aspirin (+/- clopidogrel), there were 12 spontaneous bleeds (6 minor, 6 major/life-threatening) within 90 days after assessment, with a higher risk for A+C vs. AO (8/247 vs. 4/386, p = 0.047 overall; 5/247 vs. 1/386, p = 0.03 for major/life-threatening bleeds). The excess of major/life-threatening bleeds on A+C vs. AO was seen in aspirin-naïve patients, (4/137 vs. 0/273, p = 0.01), but not in prior-aspirin patients (1/110 vs. 1/113, p = 0.98). All symptomatic bleeds in the FASTER pilot also occurred in aspirin-naïve patients randomized to A+C (6/104 vs. 0/94, p = 0.03). In a pooled analysis, major/life-threatening bleeding on A+C occurred in 9/241 aspirin-naïve patients (90-day risk = 4.8%, 1.6-8.0) versus 1/204 prior-aspirin patients (p = 0.009). CONCLUSION: Although based on relatively few outcomes, the high risk of major bleeding on A+C acutely after TIA or minor stroke in aspirin-naïve patients is a cause for concern. The potential risk to patients is sufficient to mandate detailed monitoring of bleeding risk in ongoing trials and stratify results by whether patients were aspirin-naïve.